Effects of Different Friction Control Techniques on Turbulence Developing Around Wings - Atzori, M.; Vinuesa, R.; Gatti, D.; Stroh, A.; Frohnapfel, B.; Schlatter, Philipp (Springer, 2020)
Developing efficient flow control techniques remain a challenging task due to the complexity of turbulent flows in industrial applications, a relevant example of which are turbulent boundary layers (TBL) subjected to pressure gradients. In the present study, we employ high-fidelity numerical simulations to assess the impact of different control strategies on the flow around a NACA4412 airfoil at a Reynolds number Rec=200,000 based on the chord length c and the inflow velocity U∞. The choice of this specific study case is motivated by the relatively weak dependence of the pressure distribution around the airfoil on the Reynolds number [6], which allows distinguishing the effects of increasing Reynolds number and those of the non-uniform adverse pressure gradient (APG).
CRIS-Team Scopus Importer:2023-03-21